Progress in the Study of Non-Coding RNAs in Multidifferentiation Potential of Dental-Derived Mesenchymal Stem Cells - Zeng, Biyun; Huang, Junhui (Frontiers in Genetics, 2022)
For decades, the desire for tissue regeneration has never been quenched. Dental- derived mesenchymal stem cells (DMSCs), with the potential of self-renewal and multi-directional differentiation, have attracted much attention in this topic. Growing evidence suggests that noncoding RNAs (ncRNAs) can activate various regulatory processes. Even with a slight decrease or increase in expression, ncRNAs can weaken or even subvert cellular fate. Therefore, a systematic interpretation of ncRNAs that guide the differentiation of DMSCs into cells of other tissue types is urgent needed. In this review, we briefly introduce the general properties and mechanisms of ncRNAs, and illustrate the pluripotency of DMSCs. Finally, we interpret the roles of ncRNAs in the differentiation of DMSCs into various tissues, such as bone, tooth, neural tissue, vessels, muscle-like tissue, etc. If revealing the intricate relationship between ncRNAs and pluripotency of DMSCs one day, the application of DMSCs in regenerative medicine and tissue engineering will be improved. our work could be an important stepping stone towards this future.